Global street code. A cross-cultural perspective on youth violence - Kurtenbach, Sebastian (Deviant behavior, 2021)
Some twenty years ago Anderson’s seminal work, The Code of the Street, was published. The theoretical approach he developed there has been used in numerous studies focusing on youth violence, and is now treated as a general explanation of youth violence in risky neighborhoods in a number of disciplines. Expanding this, an international research project has used the concepts to compare violence-related norms and beliefs of male juveniles between 16 and 21 years of age in risky neighborhoods in Germany, Bulgaria, Pakistan and South Africa. In each research site, semi-structured qualitative interviews were completed with 30 participants in risky neighborhoods. The results of the cross-cultural analysis of the 120 interviews show, resultantly, that the ‘code of the street’ as illustrated by Anderson differs significant between the countries and that many elements of the original concept are shaped by contextual dynamics. Here we further make a distinction between those elements that were found to be in confluence with the original code from those which differ as a result of cultural influence. It is thus argued that while the street code approach is helpful in understanding the street violence of juveniles, it is not a general explanation and context-specific factors play as equally important a role.